2019
DOI: 10.3389/fneur.2018.01066
|View full text |Cite
|
Sign up to set email alerts
|

Body Weight Support Combined With Treadmill in the Rehabilitation of Parkinsonian Gait: A Review of Literature and New Data From a Controlled Study

Abstract: Background: Gait disorders represent disabling symptoms in Parkinson's Disease (PD). The effectiveness of rehabilitation treatment with Body Weight Support Treadmill Training (BWSTT) has been demonstrated in patients with stroke and spinal cord injuries, but limited data is available in PD.Aims: The aim of the study is to investigate the efficacy of BWSTT in the rehabilitation of gait in PD patients.Methods: Thirty-six PD inpatients were enrolled and performed rehabilitation treatment for 4-weeks, with daily s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 47 publications
0
12
1
Order By: Relevance
“…On the other hand, a recent study did not prove a superior effect of BWSTT over conventional TT and showed that they both improved gait, balance, and disability in PD [24]. That study suggested that BWSTT might be preferred in advanced PD patients with severe postural instability, impaired balance, or orthostatic hypotension that would limit conventional TT.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, a recent study did not prove a superior effect of BWSTT over conventional TT and showed that they both improved gait, balance, and disability in PD [24]. That study suggested that BWSTT might be preferred in advanced PD patients with severe postural instability, impaired balance, or orthostatic hypotension that would limit conventional TT.…”
Section: Discussionmentioning
confidence: 94%
“…In the literature, 20% is the most widely used percentage of unweighing in BWSTT studies, as individuals with PD reported that 20% body weight support was the most comfortable among 0%, 10%, 20%, and 30% unweighted supports [23]. Researchers used either 20% [7,8] or a combination of 20% and 10% [22][23][24] unweighing in their BWSTT protocols and compared BWSTT to overground gait training [7,8,24] or traditional rehabilitation programs [22,23]. None of these studies performed blinding of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it may stimulate increased cadence and shorter strides [53,54]. Nevertheless, analyzing the gait characteristics in healthy young adults may be meaningful because several studies have reported the positive effects of gait training programs using treadmills [18][19][20][21][22][23][24][25][26]. Second, there were limitations in the direct comparisons of GV with previous studies because most previous studies focused on elderly adults (who ranged in age from 70 to 89 years).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, walking on treadmills may be more useful for the collection of data pertaining to numerous continuous walking steps in comparison with methods involving repeated and averaged patterns due to decreased space requirements, multiple repetitions of strides, and controllability of the walking speed [17]. Recently, many studies have reported the positive effects of gait training programs using treadmills on amputees [18] and pathological patients such as people suffering from cerebral palsy [19], Parkinson's disease [20][21][22][23][24][25], and spinal cord injury [26]. However, several studies reported limitations such as lack of controls [19,24,25] and relatively small samples of patients [20,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation